2013
DOI: 10.1080/03602559.2012.721441
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchic Structure and Mechanical Property of Short Glass Fiber/Isotactic Polypropylene Composites Containing β-Nucleation Agent

Abstract: The hierarchic structure of short glass fiber reinforced isotactic polypropylene (GF/iPP) composites with b-nucleating agent were investigated by wide-angle X-ray diffraction, differential scanning calorimetry, polarized light microscopy and scanning electronic microscopy measurements. It was found that the content of b-crystals was deceased due to the a-heterogeneous nucleation of glass fibers, yet its perfection was deteriorated due to the heterogeneous distribution of glass fibers caused by the processing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…3c). It is worth pointing out that 124 C is preferentially chosen here as the drawing temperature, which is above the onset of crystallization temperature of iPP samples [47]. At this temperature, the resultant structures are determined solely by recrystallization [48], without considering other factors like spontaneous crystal growth, especially at large strains.…”
Section: Engineering Stress-strain Behavior Of Bsk Ippmentioning
confidence: 99%
“…3c). It is worth pointing out that 124 C is preferentially chosen here as the drawing temperature, which is above the onset of crystallization temperature of iPP samples [47]. At this temperature, the resultant structures are determined solely by recrystallization [48], without considering other factors like spontaneous crystal growth, especially at large strains.…”
Section: Engineering Stress-strain Behavior Of Bsk Ippmentioning
confidence: 99%
“…Low density polyethylene (LDPE) is one of the most common polymer materials used in many manufacturing tools [1] . Many types of grafting polymerization techniques have been developed in recent years by gamma ray irradiation, electron beam irradiation, proton beams, ultraviolet light and plasma polymerization [2] .…”
Section: Introductionmentioning
confidence: 99%
“…The composites combined of PP with short glass fiber (SGF) are one of the most effective methods for enhancing the mechanical properties of PP significantly. [7][8][9][10][11][12] Also, it has been proved to be a considerable and successful technology by introducing SGF into the polymeric foams. Shen and Nutt 13 and Desai et al 14 reported that SGF could increase the strength and modulus of phenolic foam remarkably, and they considered that the reinforced phenolic foam composites might be used as a tough and low-cost engineering material in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The composites combined of PP with short glass fiber (SGF) are one of the most effective methods for enhancing the mechanical properties of PP significantly. 712 Also, it has been proved to be a considerable and successful technology by introducing SGF into the polymeric foams. Shen and Nutt 13 and Desai et al.…”
Section: Introductionmentioning
confidence: 99%